Nursing knowledge of people with paresis of voluntary muscles: a living scoping review protocol - Neves, Hugo (2022)
Objective: This review aims to continuously map the nursing knowledge about people with paresis of voluntary muscles in any context of care. Introduction: Muscle paresis is a condition that significantly impacts quality of life. Nurses have a crucial role in managing this condition, particularly paresis of voluntary movement muscles. However, nursing knowledge about patients with paresis of voluntary muscles is dispersed, hampering the integration of evidence within the structure of information systems. Mapping how the nursing process components are identified is the first step in creating a Nursing Clinical Information Model for this condition, capable of integrating evidence into information systems. Inclusion criteria: This scoping review will consider studies focusing on the nursing process regarding people with paresis of voluntary muscles in all care contexts. The review will include quantitative, qualitative, and mixed methods study designs, systematic reviews, clinical guidelines, dissertations, and theses. Methods: The review process will follow JBI's scoping review guidance, as well as the Cochrane Collaboration's guidance on living reviews. Screening of new literature will be performed regularly, with the review being updated according to new findings. The search strategy will map published and unpublished studies. The databases to be searched will include MEDLINE, CINAHL, Scopus, JBI Evidence Synthesis, and the Cochrane Central Register of Controlled Trials. Searches for unpublished studies will include OpenGrey and Repositorios Científicos de Acesso Aberto de Portugal. Studies published in English and Portuguese from 1975 will be considered for inclusion.